2016
DOI: 10.1016/j.nicl.2016.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Relation between functional connectivity and rhythm discrimination in children who do and do not stutter

Abstract: Our ability to perceive and produce rhythmic patterns in the environment supports fundamental human capacities ranging from music and language processing to the coordination of action. This article considers whether spontaneous correlated brain activity within a basal ganglia-thalamocortical (rhythm) network is associated with individual differences in auditory rhythm discrimination. Moreover, do children who stutter with demonstrated deficits in rhythm perception have weaker links between rhythm network funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 50 publications
2
30
0
1
Order By: Relevance
“…Finally, we observed a trend for AS to have lower scores on the music perception task, which is further evidence of perceptual differences between individuals who stutter and their fluent peers . This was true despite the fact that both groups had similar amounts of music training, and that scores on this task were relatively high.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Finally, we observed a trend for AS to have lower scores on the music perception task, which is further evidence of perceptual differences between individuals who stutter and their fluent peers . This was true despite the fact that both groups had similar amounts of music training, and that scores on this task were relatively high.…”
Section: Discussionsupporting
confidence: 57%
“…Thus, it has been suggested that stuttering behavior may be related to a timing deficit that is sensorimotor in nature . Coupled with this are studies showing deficits in rhythm perception and motor sequence learning, leading to the idea that this sensorimotor timing deficit may extend to nonspeech . A number of studies over the years have attempted to demonstrate this by examining nonspeech timing with metronome synchronization in people who stutter.…”
Section: Introductionmentioning
confidence: 99%
“…According to the broader literature in this area ( Buhusi and Meck, 2005 ; Fujioka et al, 2009 ; Kononowicz and van Rijn, 2015 ; Merchant and Bartolo, 2017 ), beta activity in the basal ganglia-thalamocortical circuits (measured by EEG/MEG from central brain locations) can be considered in relation to interval timing. Behaviorally, deficits in response timing tasks are frequently reported in people who stutter ( Ezrati-Vinacour and Levin, 2001 ; Olander et al, 2010 ; Falk et al, 2015 ) and recently it has been suggested that impairment of resting state functional connectivity is involved in time discrimination deficits in stuttering ( Chang et al, 2016 ). Since beta activity in primary and supplementary motor cortices is associated with activity of basal ganglia-thalamocortical circuit ( Kropotov, 2010 ), decreased BC of primary motor cortex in resting state beta2 adds further, albeit indirect, neural evidence for a deficit in interval timing networks in stuttering that involve the striatum.…”
Section: Discussionmentioning
confidence: 99%
“…Induced fluency through techniques such as chorus reading shows increased activity of left-hemispheric speech areas equal to normal controls. Clinicians theorized that induced fluency activates the outer cortical speech loops, bypassing the inactive striatum in the inner speech loop (Chang et al, 2016). Furthermore, the low function of the striatum in stuttering is associated with an overactive presynaptic dopamine system disrupting the selection, initiation, and execution of motor sequences necessary for fluent speech production (Wu et al, 1997).…”
Section: Imagingmentioning
confidence: 99%